الذوق اللغوي وأثره في اللغة (University of Mosul-college of Basic Education, 2008)
يهدف هذا البحث إلى التعريف بالذوق اللغوي ، الذي يعني القدرة على إدراك معاني الأشياء والنفوذ إلى أسرارها ، وقد استعمله اللغويون في وصفهم أو توجيههم أو نقدهم اللغوي، وقد يصرحون به في بعض المواضع عند الغوص في قضايا اللغة وأساليبها ، ويهدف أيضاً إلى بيان موقع الذوق اللغوي وقوته بين الأدلة التي يُحتَكَم إليها في اللغة ، إذ لم يُشَر إليه كثيراً بين الأدلة اللغوية، ثم بيان أثره في العربية وأساليبها من خلال التراث اللغوي.This research aims at presenting the linguistic sense which means the ability to comprehend the meaning of things and to penetrate into their secrets . This linguistic sense has been used by the grammarians in their description or direction or linguishing criticism , and they may have stated it in some contexts when dealing in depth with language subjects and styles . The research also aims at pointing out the position of linguistic sense and its strength among the evidences that are taken into consideration in language since the linguistic sense has not been referred to much among the linguistic evidences . The effect of the linguistic sense is also shown on Arabic language and its styles through the linguistic heritage .